Effect of Y addition on the microstructures and mechanical properties of Mg-Gd-Y-Sm-Zr alloys - Fu sanling; Li quanan; Chen Jun; Zhang Qing (Functional Materials, 2017)
The microstructure and mechanical properties of Mg–12Gd–xY–Sm–0.5Zr (x = 0, 1, 3, 5; mass%) alloys were investigated. Results showed β’-Mg5Gd phase composition evolution of Mg5(Gd,Y). The tensile strength of the alloys are better the WE54 alloy at high temperatures (200–300 °C). The optimal mechanical properties of the Mg-12Gd-3Y-1Sm-0.5Zr alloy are achieved at high temperatures, and the maximum tensile strength of this alloy is 323 MPa at 250 °C. The short heat-resisting performance of Mg–Gd–Y–Sm–Zr alloys under the high temperature will provide new scientific basis for the development of heat resistant magnesium alloys.